Symposium 10: Towards a Methodological Approach for the Analysis of Issues of Communication and Control in Networked E-Learning Discourse - Gustafson, Jenny; Hodgson, Vivien; Kehler, Louise; Mann, Sarah; Olsen, Sanne Fejfer (Proceedings of the International Conference on Networked Learning, 2004)
This paper investigates how relations of power and the exercise of control reveal themselves in the discourse of collaborative networked e-learning. It reports on the use of an adapted methodological approach from Critical Discourse Analysis (CDA) to analyse the discourse of two different e-learning pedagogic events. It draws conclusions from this for communication and control issues in networked e-learning and the relevance of CDA to networked e-learning research.